KIDNEY AND LIVER HISTOPATHOLOGY OF STRIPED CATFISH (Pangasianodon hypophthalmus) INFECTED WITH Edwardsiella tarda - Siburian, Melin; Syawal, Henni; Riauwaty , Morina (Asian Journal of Aquatic Sciences, 2022)
This research was conducted in April – June 2021in the Laboratory of Parasites and Fish Diseases, Faculty of Fisheries and Marine, Universitas Riau. Histological preparations were carried out at the Bukittinggi Veterinary Center (BVet). The aim of this study was to analyze the kidney structure of striped catfish (P.hypophthalmus) infected with Edwardsiella tarda with different bacterial densities. The benefit of this research is to provide information about changes in the structure of kidney tissue due to infection with E.tarda, so that later treatment solutions can be sought. The method used was an experimental method with a completely randomized design (CRD) consisting of 4 treatment levels and 3 replications. The treatments applied were P0 (fish not infected with E.tarda), P1 (fish infected with E.tarda at a density of 106 CFU/mL), P2 (107 CFU/mL), and P3 (108 CFU/mL). Striped catfish (P.hypophthalmus) used are 8-12 cm in size with a density of 1 fish/3 L. Infection is done by injection in the intraperitoneal as much as 0.1 mL/fish. The results of the study found that clinical symptoms caused by dull and protruding eyes, dull body surface color, flaky fins, body surface wounds, and bleeding. In histopathological observation, the kidneys with different bacterial densities experienced the highest damage at P3 (108 CFU/mL), namely necrosis, hemorrhage, and hypertrophy.